Sistem Informasi Geografis Penyebaran Lokasi Toko Bunga Berbasis Web di Kota Bandar Lampung - Yuli Syafitri (Universitas Mitra Indonesia, 2020)
AbstractInformation technology is developing very rapidly now, so that it is able to make people carry out activities easily. The presence of developing technology is targeted to get better results more easily with the accuracy of its use, one of which is the website. The website is also stored on a server in a name, namely a domain or sub domain that can connect a navigation application to find a location is GIS or Geographical Information Systems. So far the public knows the location of the flower shop through the website, Instagram and Facebook, this method causes the information obtained to be incomplete and takes a lot of time to find the location of the flower shop and the number of flower shop availability is sometimes not proportional to the number of flower shop seekers. In addition, flower shop seekers also do not have information about the location of flower shops and many immigrants do not know about the Bandar Lampung area, so they have difficulty getting to the flower shop. Based on this, the authors propose to design a geographic information system to determine the location of the web-based flower shop in Bandar Lampung. The results of this study are able to display information about flower shops, able to provide relevant information about flower shops in Lampung based on the user's location.